Equating real parts in
#e^(i4theta) = (e^(itheta))^4#,
#cos 4theta = cos^4theta - 6sin^2theta cos^2theta + sin^4theta#
#= (sin^2theta +cos^2theta )^2 - 8 sin^2theta cos^2theta#
#= 1 - 8 sin^2theta cos^2theta#. So,
#cos 4theta - sin2theta + tan 2theta#
#= 1 - 8 sin^2theta cos^2theta - 2sin theta cos theta #
#+ (2tan theta)/( 1 - tan^2theta )#
#= .1 - 8 sin^2theta cos^2theta - 2sin theta cos theta #
#+ (2 sin theta cos theta)/( cos^2theta - sin^2theta )#
#= .1 - 8 sin^2theta cos^2theta#
# - 2sin theta cos theta ( 1 - ( sin^2theta + cos^2theta )/(cos^2theta - sin^2theta ))#
#= 1 - 8 sin^2theta cos^2theta + (4 sin^3theta cos theta )/( cos^2 theta - sin^2theta )#